2022
DOI: 10.34172/jpe.2022.29187
|View full text |Cite
|
Sign up to set email alerts
|

Human monkeypox companionship and sexually transmitted diseases; lessons from the HIV pandemic for monkeypox response

Abstract: There are many unknowns and much uncertainty in connection with the recent monkeypox (MPX) outbreak. But is the world ready for a new common viral disease? The aim of this study was to investigate the effects of MPX companionship and STI diseases and in lessons where the HIV pandemic can be used to control MPX outbreaks. A critical literature review, based on the findings from 12 primary research articles. Explores the effects of MPX outbreak on HIV and the lessons that can be used from HIV to control MPX outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Regarding the severity of illness, studies from previous mpox outbreaks in Nigeria during 2017-2018 reported a case fatality rate of 6%, from which 4 among 7 deaths involved patients with HIV/AIDS. 3 Studies on recent outbreaks showed the disease is mild and self-limited. 11 Patients who required hospitalization were more likely to be HIV positive and the most common cause of hospitalization was pain control and bacterial superinfection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the severity of illness, studies from previous mpox outbreaks in Nigeria during 2017-2018 reported a case fatality rate of 6%, from which 4 among 7 deaths involved patients with HIV/AIDS. 3 Studies on recent outbreaks showed the disease is mild and self-limited. 11 Patients who required hospitalization were more likely to be HIV positive and the most common cause of hospitalization was pain control and bacterial superinfection.…”
Section: Discussionmentioning
confidence: 99%
“…The most affected population are men who have sex with men (MSM), and these have shown to have worse outcomes in the setting of uncontrolled HIV infection. 3 An mpox outbreak in 2017 in Nigeria reported a case fatality rate of 6% (7/118), of which four cases had uncontrolled HIV with features of AIDS, low CD4 count (below 200 cells/mm 3 ), or a recent HIV-related illness. 4 Data from the 2022 multinational outbreak showed a high HIV prevalence (38%) in mpox infected patients as well as high prevalence of one or more other reportable STIs in the preceding year (41%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sociocultural aspects of the Mpox pandemic have been significant in shaping men's experiences, highlighting social distancing as a crucial measure for disease control. However, while effective for health, this measure presents challenges such as prolonged confinement and disruption of social bonds, particularly in the context of the COVID-19 pandemic (Bergman et al, 2022;Hraib et al, 2022;Pourrezaei et al, 2023). Understanding the role of misinformation is essential in understanding the dynamics of Mpox among Brazilian men.…”
Section: Challenges and The Need For Interventionmentioning
confidence: 99%